Early-Phase Recovery of Cardiorespiratory Measurements after Maximal Cardiopulmonary Exercise Testing in Patients with Chronic Obstructive Pulmonary Disease - Bellefleur, Marie; Debeaumont, David; Boutry, Alain; Netchitailo, Marie; Cuvelier, Antoine; Muir, Jean-François; Tardif, Catherine; Coquart, Jérémy (Pulmonary Medicine, 2016)
Background. This study investigated respiratory gas exchanges and heart rate (HR) kinetics during early-phase recovery after a maximal cardiopulmonary exercise test (CPET) in patients with chronic obstructive pulmonary disease (COPD) grouped according to airflow limitation. Methods. Thirty control individuals (control group: CG) and 81 COPD patients (45 with “mild” or “moderate” airflow limitation, COPDI-II, versus 36 with “severe” or “very severe” COPD, COPDIII-IV) performed a maximal CPET. The first 3 min of recovery kinetics was investigated for oxygen uptake (V˙O2), minute ventilation (V˙E), respiratory equivalence, and HR. The time for V˙O2 to reach 25% (T1/4V˙O2) of peak value was also determined and compared. Results. The V˙O2, V˙E, and HR recovery kinetics were significantly slower in both COPD groups than CG (p<0.05). Moreover, COPDIII-IV group had significantly higher V˙O2 and V˙E during recovery than COPDI-II group (p<0.05). T1/4V˙O2 significantly differed between groups (p<0.01; 58±18 s in CG, 79±26 s in COPDI-II group, and 121±34 s in COPDIII-IV) and was significantly correlated with forced expiratory volume in one second in COPD patients (p<0.001, r=0.53) and with peak power output (p<0.001, r=0.59). Conclusion. The COPD groups showed slower kinetics in the early recovery period than CG, and the kinetics varied with severity of airflow obstruction.